Digital Flood Control Model as a Digital Practical Learning Module - widodo, sarono; Wasito, Endro; Anggraeni, Sri; Prahara, Tahan; Yulianto, Taufiq (JAICT, 2025)
Abstract”” Teaching aids are one of the learning media that can be used in the learning process in the classroom or laboratory. The purpose of this media is to facilitate the understanding of the material being studied. In laboratory learning, in addition to practical modules, the development of teaching aids is needed as a case study for solving problems in the field. The teaching aid being researched is a learning module as the development of digital engineering practicals in the laboratory, specifically a digital flood control module. The module designed and created aims to teach how a flood control process can be created using digital circuits, thereby providing insights and understanding to students about the control process. The controller module reads the water level sensors set at high and low levels. When the water touches the high-level water sensor, the control output activates the relay to turn on the pump, so the water in a specific location is pumped elsewhere. When the control system reads the low-level sensor, the output deactivates the relay and the pump stops working. The water level sensor is set at a distance of 10 cm between the lower and upper limits. The volume of water pumped is 0.006 m3 or 6 liters in 30 seconds using a 12v DC water pump with a power of 25 watts.